Porous three-phase alloy and its application, high bio-based elastomer tire apex rubber composition

By using porous three-phase alloys to improve the performance of triangular glue, the problems of poor thermal conductivity and insufficient heat resistance of existing triangular glues are solved, and higher thermal conductivity, mechanical strength and environmental friendliness are achieved.

CN118910477BActive Publication Date: 2025-03-07ZHONGCE RUBBER GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411377110.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-03-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing triangular glue has poor thermal conductivity and insufficient heat resistance, which leads to an increase in the risk of overheating of the tire, affecting its service life and safety. At the same time, its preparation raw materials are mainly petroleum and petrochemical products, which are difficult to meet the requirements of green and environmental protection.

Method used

A porous three-phase alloy is prepared from carbon black and natural ore powder by high temperature jet treatment to form an aluminum-silicon-carbon aggregate and is applied to a high-biologically based elastomer triangular rubber composition.

Benefits of technology

It improves the thermal conductivity, mechanical strength and high temperature resistance of triangular glue, reduces the thermal expansion coefficient, and enhances environmental friendliness and sustainable development capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118910477B_ABST
    Figure CN118910477B_ABST
Patent Text Reader

Abstract

The present invention provides a porous three-phase alloy and its application, and a high bio-based elastomer tire apex rubber composition, which specifically relates to the technical field of tire manufacturing. The porous three-phase alloy is mainly obtained by high-temperature jetting of carbon black and natural ore powder; the content of silicon dioxide in the natural ore powder is 40-60%, and the content of aluminum oxide is 30-40%; the specific surface area of ​​the natural ore powder is 30-70m 2 / g, pore volume 0.20~0.40cm 3 / g, the number of pores is 100-300 million / g, and the D50 particle size is 0.25-5 μm. The porous three-phase alloy provided by the present invention is a new type of aluminum-silicon-carbon aggregate, which not only has high hardness and wear resistance, but also has a low thermal expansion coefficient, which is conducive to maintaining the dimensional stability of the rubber composition under high temperature environment. The aluminum-silicon-carbon aggregate performs well in interface bonding, reduces the interface thermal resistance, and thus improves the thermal conduction efficiency of the aggregate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tire manufacturing, in particular to a porous three-phase alloy and application thereof, and a high-biobased elastomer tire apex rubber composition. Background Art

[0002] As a key component on both sides of the tire tread centerline, the triangular design of the apex not only achieves a transition between the sidewall and the bead, but also effectively protects the tire and extends its service life by enhancing the rigidity and wear resistance of the tread. However, during the operation of the tire, the friction between the apex and the bead and the heat generated by the bead will cause heat accumulation, increasing the risk of tire overheating. Long-term high temperature environment may cause the apex to age or degrade, thereby affecting the performance and life of the tire, and even affecting driving safety.

[0003] In the existing preparation process of apex rubber, the raw materials used have poor thermal conductivity and insufficient heat resistance, resulting in the performance of the final product being unable to meet higher requirements, affecting the service life of the tire, increasing the frequency of replacement, and reducing the user experience.

[0004] In addition, most of the raw materials used to make apex rubber come from petroleum and petrochemical products, which do not meet the requirements of bio-based raw materials and are difficult to meet the requirements of green and environmental protection. They may have a negative impact on the environment after the tire's service life ends. At the same time, when trying to use bio-based carbon as an alternative raw material, it will cause problems such as slow sulfur rate and low thermal conductivity. Even if the amount of vulcanizer is increased to increase the sulfur rate, it will cause the rubber to become brittle, and the heat resistance and physical properties will deteriorate, further affecting the overall performance of the apex rubber.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One of the objectives of the present invention is to provide a porous three-phase alloy to alleviate at least one of the above-mentioned technical problems in the prior art.

[0007] A second object of the present invention is to provide an application of a porous three-phase alloy.

[0008] A third object of the present invention is to provide a high bio-based elastomer tire apex rubber composition.

[0009] A fourth object of the present invention is to provide a high bio-based elastomer tire apex rubber.

[0010] In order to solve the above-mentioned technical problems, the present invention particularly adopts the following technical solutions:

[0011] A first aspect of the present invention provides a porous three-phase alloy, wherein the porous three-phase alloy is mainly obtained by high-temperature jetting of carbon black and natural ore powder.

[0012] The content of silicon dioxide in the natural ore powder is 40-60%, and the content of aluminum oxide is 30-40%.

[0013] The natural ore powder has a rich microporous structure and a specific surface area of ​​30-70m 2 / g, pore volume 0.20~0.40cm 3 / g, the number of pores is 100-300 million / g, and the D50 particle size is 0.25-5μm.

[0014] Furthermore, the mass ratio of the carbon black to the natural ore powder is 5-9:1-5.

[0015] The grades of the carbon black include at least one of N134, N220, N234, N330, N375 and N550.

[0016] Furthermore, the high temperature jet process includes:

[0017] The natural ore powder suspension mixed by the jet system is sprayed into the carbon black reaction furnace, and the carbon black reacts with the natural ore powder to generate an aluminum-silicon-carbon structure, which is aggregated to form an aluminum-silicon-carbon aggregate to obtain the porous three-phase alloy.

[0018] The concentration of the natural ore powder suspension is 15-25wt.%.

[0019] The injection flow rate of the natural ore powder suspension is 4000-6000 kg / h.

[0020] The reaction temperature is 1000-1500°C.

[0021] The second aspect of the present invention provides the use of the porous three-phase alloy in the preparation of a high-biobased elastomer tire apex rubber composition.

[0022] The third aspect of the present invention provides a high bio-based elastomer tire apex rubber composition, which comprises, by weight:

[0023] 100 parts of natural rubber, 5-20 parts of the porous three-phase alloy described in the first aspect, 20-40 parts of rice husk ash white carbon black, 1-4 parts of silane coupling agent, 3-6 parts of activator, 2-6 parts of antioxidant, 1-3 parts of tackifying resin, 2.5-4.7 parts of insoluble sulfur, 0.8-1.5 parts of accelerator and 0.1-0.5 parts of super vulcanizing aid.

[0024] Furthermore, the super vulcanization aid is a low eutectic solvent.

[0025] The super vulcanization aid is mainly prepared from zinc chloride, choline chloride and thiourea in a molar ratio of 1-3:1-3:3-6.

[0026] Furthermore, the specific surface area of ​​the rice husk gray carbon black is 165~240m 2 / g, particle size is 0.8~7.8μm.

[0027] The brands of the silane coupling agent include at least one of TESPT, Si75 and Si747.

[0028] The activators include stearic acid and / or zinc oxide.

[0029] The brands of the antioxidant include at least one of antioxidant 4020, antioxidant RD and antioxidant 4010NA.

[0030] The tackifying resin includes at least one of tert-butylphenol-formaldehyde resin, alkylphenol-formaldehyde resin and petroleum resin.

[0031] Preferably, the grades of the petroleum resin include C5 and / or C9.

[0032] The brands of the accelerator include at least one of accelerator NS, accelerator CZ and accelerator DZ.

[0033] The fourth aspect of the present invention provides a high bio-based elastomer tire apex rubber, which is mainly obtained by mixing the high bio-based elastomer tire apex rubber composition described in the third aspect.

[0034] Furthermore, the mixing method comprises the following steps:

[0035] The first masterbatch is obtained by mixing natural rubber, porous three-phase alloy material, rice husk gray carbon black, silane coupling agent, antioxidant and tackifying resin and performing a mixing step;

[0036] Then, the first masterbatch is subjected to two-stage mixing to obtain a second masterbatch;

[0037] Finally, insoluble sulfur, accelerator and super vulcanizing aid are added into the second masterbatch and mixed and then three-stage kneading is performed to obtain high bio-based elastomer tire apex rubber.

[0038] Furthermore, the first stage of mixing includes mixing for 30-50 seconds, mixing with the plug lifted and pressed for 20-30 seconds, and then mixing with the plug lifted and pressed to 140-155° C. for debonding in this order.

[0039] The two-stage mixing includes mixing for 30-50 seconds, mixing with the plug lifted and the plug pressed for 20-30 seconds, and then mixing with the plug lifted and the plug pressed until the temperature reaches 135-145° C. for debonding.

[0040] The three-stage mixing includes mixing for 30-50 seconds, mixing with the plug lifted and the plug pressed for 20-30 seconds, and then mixing with the plug lifted and the plug pressed until the temperature reaches 95-105° C. for debonding.

[0041] Compared with the prior art, the present invention has at least the following beneficial effects:

[0042] The porous three-phase alloy provided by the present invention forms a new type of aluminum-silicon-carbon aggregate by imparting the advantageous properties of carbon black to natural ore powder. This aggregate not only has high hardness and wear resistance, but also has a low thermal expansion coefficient, which is conducive to maintaining the dimensional stability of the rubber composition under high temperature conditions. At the same time, the aggregate exhibits excellent high temperature resistance and can maintain its mechanical properties under extreme temperature conditions. The high thermal conductivity of aluminum makes the formed aluminum-silicon-carbon aggregate perform well in interface bonding, reduces the interface thermal resistance, and thus improves the thermal conduction efficiency of the aggregate. In addition, the thermal expansion coefficients of aluminum, silicon and carbon are relatively matched, which reduces the thermal stress caused by uneven thermal expansion and further promotes the stable transfer of thermal energy. The role of silicon and carbon particles in the aggregate is to reduce thermal resistance, improve the efficiency of the heat conduction path, and make the overall aggregate perform well in heat conduction.

[0043] The application of the porous three-phase alloy provided by the present invention, in view of the advantages of the above-mentioned porous three-phase alloy, enables the prepared high-biobased elastomer tire apex rubber composition to have better thermal conductivity and mechanical strength and a lower thermal expansion coefficient.

[0044] The high-biobased elastomer tire apex rubber composition provided by the present invention uses natural rubber as the basis, which increases the biobased content in the rubber composition and reduces the dependence on fossil fuels. At the same time, the addition of bio-based carbon black reduces the use cost of carbon black, reduces environmental pollution, saves fossil resources, and realizes the sustainable development of the rubber industry. Bio-based carbon black causes problems such as poor physical properties, slow sulfur rate, and low efficiency. The use of super vulcanization aids can perfectly solve this problem and improve vulcanization efficiency and vulcanization quality. At the same time, the addition of porous three-phase alloy makes the rubber composition have low heat generation, high thermal conductivity and excellent heat resistance, which improves the performance of rubber products. The raw materials in the composition cooperate with each other, so that the rubber composition has significant technical effects in improving rubber performance and enhancing environmental friendliness.

[0045] The high-biobased elastomer tire apex rubber provided by the present invention, in view of the advantages of the above-mentioned rubber composition, enables the prepared apex rubber to have better performance and be more environmentally friendly, meets the performance requirements of different fields, and promotes the development of the tire industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0047] Figure 1 This is a scanning electron microscope image at a magnification obtained in Characterization Example 1;

[0048] Figure 2 This is a scanning electron microscope image at another magnification obtained in Characterization Example 1;

[0049] Figure 3 This is a scanning electron microscope image at the third magnification obtained in Characterization Example 1. DETAILED DESCRIPTION

[0050] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the embodiment of the present invention will be clearly and completely described below in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, but not all of the embodiments. The components of the embodiment of the present invention can be arranged and designed in various different configurations.

[0051] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0052] A first aspect of the present invention provides a porous three-phase alloy, wherein the porous three-phase alloy is mainly obtained by high-temperature jetting of carbon black and natural ore powder.

[0053] The content of silicon dioxide in the natural ore powder is 40-60%, and the content of aluminum oxide is 30-40%.

[0054] The natural ore powder has a rich microporous structure and a specific surface area of ​​30-70m 2 / g, pore volume 0.20~0.40cm 3 / g, the number of pores is 100-300 million / g, and the D50 particle size is 0.25-5μm.

[0055] The porous three-phase alloy provided by the present invention forms a new type of aluminum-silicon-carbon aggregate by imparting the advantageous properties of carbon black to natural ore powder. This aggregate not only has high hardness and wear resistance, but also has a low thermal expansion coefficient, which is conducive to maintaining the dimensional stability of the rubber composition under high temperature conditions. At the same time, the aggregate exhibits excellent high temperature resistance and can maintain its mechanical properties under extreme temperature conditions. The high thermal conductivity of aluminum makes the formed aluminum-silicon-carbon aggregate perform well in interface bonding, reduces the interface thermal resistance, and thus improves the thermal conduction efficiency of the aggregate. In addition, the thermal expansion coefficients of aluminum, silicon and carbon are relatively matched, which reduces the thermal stress caused by uneven thermal expansion and further promotes the stable transfer of thermal energy. The role of silicon and carbon particles in the aggregate is to reduce thermal resistance, improve the efficiency of the heat conduction path, and make the overall aggregate perform well in heat conduction.

[0056] The present invention limits the content of silicon dioxide and aluminum oxide in the natural ore powder in order to ensure a reasonable ratio of each raw material in the aluminum-silicon-carbon aggregate, thereby optimizing the performance of the porous three-phase alloy.

[0057] Typically but not limiting, the content of silicon dioxide in the natural ore powder can be 40%, 45%, 50%, 55%, 60%, or any value in the range of 40% to 60%; the content of aluminum oxide can be 30%, 35%, 40%, or any value in the range of 30% to 40%.

[0058] The present invention limits the specific surface area, pore volume, number of pores and D50 particle size of the natural mineral powder in order to ensure the rich pore structure of the natural mineral powder, so as to increase the growth of carbon black primary particles on the pore surface, secondly, to facilitate the combination of the rubber molecular chain ends with the pores, and thirdly, the particle size of the mineral powder and the carbon black particle size form a gradient particle size distribution.

[0059] Furthermore, the mass ratio of the carbon black to the natural ore powder is 5-9:1-5.

[0060] The mass ratio of carbon black to natural mineral powder is controlled within the range of 5~9:1~5 to ensure that the primary carbon black particles are coated on the surface of the natural mineral powder with a porous structure, rather than the natural mineral powder coating the carbon black. The prepared filler has a good reinforcement effect.

[0061] Typically but not limiting, the mass ratio of carbon black to natural ore powder can be 5:5, 6:4, 7:3, 8:2, 9:1, or any value within the range of 5-9:1-5.

[0062] The grades of the carbon black include at least one of N134, N220, N234, N330, N375 and N550.

[0063] Furthermore, the high temperature jet process includes:

[0064] The natural ore powder suspension mixed by the jet system is sprayed into the carbon black reaction furnace, and the carbon black reacts with the natural ore powder to generate an aluminum-silicon-carbon structure, which is aggregated to form an aluminum-silicon-carbon aggregate to obtain the porous three-phase alloy.

[0065] The concentration of the natural ore powder suspension is 15-25wt.%.

[0066] The injection flow rate of the natural ore powder suspension is 4000-6000 kg / h.

[0067] The reaction temperature is 1000-1500°C.

[0068] During the high-temperature jet process, carbon black particles grow in situ on the porous material to form a carbon black coating.

[0069] Typically but not limiting, the concentration of the natural ore powder suspension can be 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%, 21wt.%, 22wt.%, 23wt.%, 24wt.% or 25wt.%, or it can be any value within the range of 15wt.% to 25wt.%.

[0070] Typically but not limiting, the injection rate of the natural ore powder suspension can be 4000 kg / h, 4500 kg / h, 5000 kg / h, 5500 kg / h, 6000 kg / h, or any value within the range of 4000 kg / h to 6000 kg / h.

[0071] Likewise, the reaction temperature may be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, or any value within the range of 1000°C to 1500°C.

[0072] The second aspect of the present invention provides the use of the porous three-phase alloy in the preparation of a high-biobased elastomer tire apex rubber composition.

[0073] The application of the porous three-phase alloy provided by the present invention, in view of the advantages of the above-mentioned porous three-phase alloy, enables the prepared high-biobased elastomer tire apex rubber composition to have better thermal conductivity and mechanical strength and a lower thermal expansion coefficient.

[0074] The third aspect of the present invention provides a high bio-based elastomer tire apex rubber composition, which comprises, by weight:

[0075] 100 parts of natural rubber, 5-20 parts of the porous three-phase alloy described in the first aspect, 20-40 parts of rice husk ash white carbon black, 1-4 parts of silane coupling agent, 3-6 parts of activator, 2-6 parts of antioxidant, 1-3 parts of tackifying resin, 2.5-4.7 parts of insoluble sulfur, 0.8-1.5 parts of accelerator and 0.1-0.5 parts of super vulcanizing aid.

[0076] The high-biobased elastomer tire apex rubber composition provided by the present invention uses natural rubber as the basis, which increases the biobased content in the rubber composition and reduces the dependence on fossil fuels. At the same time, the addition of bio-based carbon black reduces the use cost of carbon black, reduces environmental pollution, saves fossil resources, and realizes the sustainable development of the rubber industry. Bio-based carbon black causes problems such as poor physical properties, slow sulfur rate, and low efficiency. The use of super vulcanization aids can perfectly solve this problem and improve vulcanization efficiency and vulcanization quality. At the same time, the addition of porous three-phase alloy makes the rubber composition have low heat generation, high thermal conductivity and excellent heat resistance, which improves the performance of rubber products. The raw materials in the composition cooperate with each other, so that the rubber composition has significant technical effects in improving rubber performance and enhancing environmental friendliness.

[0077] The high bio-based elastomer tire apex rubber composition achieves remarkable technical effects through a carefully designed formula and process, as described in detail as follows:

[0078] This composition is based on natural rubber, which is a large commercial bio-based rubber obtained directly from nature. The entire composition has a high bio-based content, which helps reduce dependence on fossil fuels and meets the requirements of sustainable development and environmental protection. The wear resistance of the rubber is significantly improved by adding porous three-phase alloys. The high hardness and wear resistance of the porous three-phase alloy effectively improve the wear resistance of the rubber and extend the service life of rubber products.

[0079] The addition of rice husk ash white carbon black not only improves the hardness and wear resistance of rubber, but also significantly improves its thermal stability, allowing the rubber to maintain stable size and performance under high temperature environment. The addition of silane coupling agent and activator improves the processing performance of rubber, making it easier to operate during mixing and molding, while enhancing the combination of filler and rubber substrate and improving the mechanical properties of rubber.

[0080] The addition of antioxidants effectively delays the aging process of rubber and extends its service life. It captures free radicals, inhibits oxidation reactions, and reduces the aging of rubber due to ultraviolet radiation or high temperature. The addition of tackifying resins improves the adhesion of rubber, making it perform better in combination with other materials, which is very important for application scenarios that require high adhesion performance.

[0081] The combined use of insoluble sulfur, accelerators and super vulcanizing aids optimizes the vulcanization process of rubber, improves the vulcanization efficiency and quality, and helps the rubber form a more uniform and stable cross-linking structure during the vulcanization process, thereby improving the overall performance of the rubber.

[0082] In addition, the porous three-phase alloy and rice husk ash white carbon black used in the rubber composition are both environmentally friendly. Rice husk ash white carbon black, as a bio-based carbon black, is almost insoluble in the soil, which helps to reduce environmental pollution.

[0083] Through reasonable proportioning and optimized formula, the rubber composition not only performs well in the basic performance of rubber products, but can also be adjusted according to specific application needs to meet the performance requirements of different fields. In short, this high-biobased elastomer tire apex rubber composition has significant technical effects in improving rubber performance, enhancing environmental friendliness and promoting sustainable development.

[0084] Typically but not limiting, the rubber composition comprises 100 parts of natural rubber; 5 parts, 10 parts, 15 parts or 20 parts by weight of porous three-phase alloy; 20 parts, 25 parts, 30 parts, 35 parts or 40 parts by weight of rice husk ash and white carbon black; 1 part, 2 parts, 3 parts or 4 parts by weight of silane coupling agent; 3 parts, 4 parts, 5 parts or 6 parts by weight of activator; and 100 parts by weight of antioxidant. For example, it can be 2 parts, 3 parts, 4 parts, 5 parts or 6 parts; the weight portion of the tackifying resin can be, for example, 1 part, 2 parts or 3 parts; the weight portion of the insoluble sulfur can be, for example, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts or 4.7 parts; the weight portion of the accelerator can be, for example, 0.8 parts, 1.0 parts, 1.2 parts or 1.5 parts; the weight portion of the super vulcanization aid can be, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts.

[0085] Furthermore, the super vulcanization aid is a low eutectic solvent.

[0086] The super vulcanization aid is mainly prepared from zinc chloride, choline chloride and thiourea in a molar ratio of 1-3:1-3:3-6.

[0087] The low eutectic solvent is prepared by mixing zinc chloride, choline chloride and thiourea in a certain proportion to form a liquid molten state at a temperature lower than the melting point of each individual substance. The melting point of the obtained low eutectic solvent is lower than the melting point of each component.

[0088] Typically but not limiting, the molar ratio of zinc chloride, choline chloride and thiourea can be 1:1:3, 1:2:4, 1:3:6 or 3:3:6, or any ratio combination within the range of 1-3:1-3:3-6.

[0089] Furthermore, the specific surface area of ​​the rice husk gray carbon black is 165~240m 2 / g, particle size is 0.8~7.8μm.

[0090] Typically, but not limiting, the specific surface area of ​​the rice husk ash white carbon black may be 165 m 2 / g, 170 m 2 / g, 180m 2 / g, 190 m 2 / g, 200 m 2 / g, 210 m 2 / g, 220 m 2 / g, 230 m 2 / g or 240 m 2 / g, or 165 m 2 / g ~240 m 2 / g; the particle size of rice husk gray white carbon black can be 0.8 μm, 1.0 μm, 1.5 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm or 7.8 μm, or it can be any value in the range of 0.8 μm ~7.8 μm.

[0091] The brands of the silane coupling agent include at least one of TESPT, Si75, OTES and Si747.

[0092] The activators include stearic acid and / or zinc oxide.

[0093] The brands of the antioxidant include at least one of antioxidant 4020, antioxidant RD and antioxidant 4010NA.

[0094] The tackifying resin includes at least one of tert-butylphenol-formaldehyde resin, alkylphenol-formaldehyde resin and petroleum resin.

[0095] Preferably, the grades of the petroleum resin include C5 and / or C9.

[0096] The brands of the accelerator include at least one of accelerator NS, accelerator CZ and accelerator DZ.

[0097] The fourth aspect of the present invention provides a high bio-based elastomer tire apex rubber, which is mainly obtained by mixing the high bio-based elastomer tire apex rubber composition described in the third aspect.

[0098] The high-biobased elastomer tire apex rubber provided by the present invention, in view of the advantages of the above-mentioned rubber composition, enables the prepared apex rubber to have better performance and be more environmentally friendly, meets the performance requirements of different fields, and promotes the development of the tire industry.

[0099] Furthermore, the mixing method comprises the following steps:

[0100] The first masterbatch is obtained by mixing natural rubber, porous three-phase alloy material, rice husk gray carbon black, silane coupling agent, antioxidant and tackifying resin and performing a mixing step;

[0101] Then, the first masterbatch is subjected to two-stage mixing to obtain a second masterbatch;

[0102] Finally, insoluble sulfur, accelerator and super vulcanizing aid are added into the second masterbatch and mixed and then three-stage kneading is performed to obtain high bio-based elastomer tire apex rubber.

[0103] Furthermore, the first stage of mixing includes mixing for 30-50 seconds, mixing with the plug lifted and pressed for 20-30 seconds, and then mixing with the plug lifted and pressed to 140-155° C. for debonding in this order.

[0104] The two-stage mixing includes mixing for 30-50 seconds, mixing with the plug lifted and the plug pressed for 20-30 seconds, and then mixing with the plug lifted and the plug pressed until the temperature reaches 135-145° C. for debonding.

[0105] The three-stage mixing includes mixing for 30-50 seconds, mixing with the plug lifted and the plug pressed for 20-30 seconds, and then mixing with the plug lifted and the plug pressed until the temperature reaches 95-105° C. for debonding.

[0106] Typically but not limiting, the temperature and time of the mixing process can be specifically as follows: the initial mixing stage can last for 30s, 35s, 40s or 50s, followed by the bolt lifting and bolt pressing mixing, which can last for 20s, 25s or 30s. After the bolt lifting and bolt pressing mixing is completed, the mixing is continued until the rubber temperature reaches 140°C, 143°C, 145°C or 155°C when the rubber is discharged.

[0107] Typically but not limiting, the temperature and time of the two-stage mixing process can be specifically as follows: the initial mixing stage can last for 30s, 35s, 40s or 50s, followed by the bolt lifting and bolt pressing mixing, which can last for 20s, 25s or 30s. After the bolt lifting and bolt pressing mixing is completed, the mixing is continued until the rubber temperature reaches 135°C, 138°C, 141°C or 145°C, and the rubber is discharged.

[0108] Typically but not limiting, the temperature and time of the three-stage mixing process can be specifically as follows: the initial mixing stage can last for 30s, 35s, 40s or 50s, followed by the bolt lifting and bolt pressing mixing, which can last for 20s, 25s or 30s. After the bolt lifting and bolt pressing mixing is completed, the mixing is continued until the rubber temperature reaches 95°C, 98°C, 101°C or 105°C, and the rubber is discharged.

[0109] In the following, some embodiments of the present invention are described in detail in conjunction with the embodiments. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0110] The raw materials used in the examples and comparative examples are shown in Table 1 below.

[0111] Table 1

[0112]

[0113] Example 1

[0114] This embodiment provides a porous three-phase alloy, and the preparation method is as follows:

[0115] In the jet system, the natural ore powder and process water are mixed evenly by powder injection technology, and the concentration of the natural ore powder suspension is controlled to be 20wt.%. The natural ore powder suspension is then sprayed into the carbon black reactor by the jet system, with a spray flow rate of 5000kg / h, and the mass ratio of carbon black to natural ore powder is controlled to be 8:2. The temperature in the carbon black reactor is set to 1000°C. Carbon black reacts with natural ore powder to form an aluminum-silicon-carbon structure, which is aggregated to form an aluminum-silicon-carbon aggregate to obtain the porous three-phase alloy.

[0116] Example 2

[0117] This embodiment provides a porous three-phase alloy, and the preparation method is as follows:

[0118] In the jet system, the natural ore powder and process water are mixed evenly by powder injection technology, and the concentration of the natural ore powder suspension is controlled to be 15wt.%. The natural ore powder suspension is then sprayed into the carbon black reactor by the jet system, with a spray flow rate of 6000kg / h, and the mass ratio of carbon black to natural ore powder is controlled to be 8:2. The temperature in the carbon black reactor is set to 1200°C. Carbon black reacts with natural ore powder to form an aluminum-silicon-carbon structure, which is aggregated to form an aluminum-silicon-carbon aggregate to obtain the porous three-phase alloy.

[0119] Example 3

[0120] This embodiment provides a porous three-phase alloy, and the preparation method is as follows:

[0121] In the jet system, the natural ore powder and process water are mixed evenly by powder injection technology, and the concentration of the natural ore powder suspension is controlled to be 25wt.%. The natural ore powder suspension is then sprayed into the carbon black reactor by the jet system, with a spray flow rate of 4000kg / h, and the mass ratio of carbon black to natural ore powder is controlled to be 8:2. The temperature in the carbon black reactor is set to 1500°C. Carbon black reacts with natural ore powder to form an aluminum-silicon-carbon structure, which is aggregated to form an aluminum-silicon-carbon aggregate to obtain the porous three-phase alloy.

[0122] Example 4

[0123] This embodiment provides a porous three-phase alloy. Different from the embodiment, the mass ratio of carbon black to natural ore powder is 7:3, and the remaining raw materials and steps are the same as those in embodiment 1, which will not be repeated here.

[0124] Example 5

[0125] This embodiment provides a porous three-phase alloy. Different from the embodiment, the mass ratio of carbon black to natural ore powder is 9:1, and the remaining raw materials and steps are the same as those in embodiment 1, which will not be repeated here.

[0126] Example 6

[0127] This embodiment provides a porous three-phase alloy. Different from the embodiment, the mass ratio of carbon black to natural ore powder is 6:4, and the remaining raw materials and steps are the same as those in embodiment 1, which will not be repeated here.

[0128] Example 7

[0129] This embodiment provides a porous three-phase alloy. Different from the embodiment, the mass ratio of carbon black to natural ore powder is 5:5, and the remaining raw materials and steps are the same as those in embodiment 1, which will not be repeated here.

[0130] Example 8

[0131] This embodiment provides a porous three-phase alloy. Different from the embodiment, the mass ratio of carbon black to natural ore powder is 2:8, and the remaining raw materials and steps are the same as those in embodiment 1, which will not be repeated here.

[0132] Test Example 1

[0133] The porous three-phase alloys obtained in Examples 1 to 8 were subjected to performance tests, specifically including thermal conductivity and thermal expansion coefficient measurements.

[0134] The thermal conductivity shall be determined in accordance with the provisions of GB / T 8722-2019; the thermal expansion coefficient shall be determined in accordance with the provisions of GB / T9966.16-2021.

[0135] The obtained results are shown in Table 2 below.

[0136] Table 2

[0137]

[0138] It can be seen from Table 2 that the thermal conductivity of the porous three-phase alloy is 0.223W / m·K~0.288W / m·K, and the thermal expansion coefficient is 0.11 / °C~0.18 / °C.

[0139] Characterization Example 1

[0140] The porous three-phase alloy obtained in Example 1 was subjected to a scanning electron microscope, and the obtained image is as follows Figure 1 , Figure 2 and Figure 3 As shown. Figure 1-Figure 3 It can be seen that the carbon black is organically complexed with the porous mineral powder.

[0141] Examples 9-13 and Comparative Examples 1-2

[0142] These embodiments provide a high bio-based elastomer tire apex rubber, which is made of a high bio-based elastomer tire apex rubber composition, and the formula of the high bio-based elastomer tire apex rubber composition is shown in Table 3. The porous three-phase alloy used is the porous three-phase alloy provided in Example 4.

[0143] Table 3

[0144]

[0145] Note: “ / ” indicates that the substance is not added.

[0146] In the above-mentioned Examples 9 to 13, the super vulcanization aid DES is obtained by melting zinc chloride, choline chloride and thiourea in a molar ratio of 1:1:4.

[0147] Embodiment 14

[0148] This embodiment provides a high bio-based elastomer tire apex rubber, wherein the formula of the high bio-based elastomer tire apex rubber composition is different from that of Example 9 in that the super vulcanizing agent DES is obtained by co-melting zinc chloride, choline chloride and thiourea in a molar ratio of 1:1:3, and other raw materials and methods are the same as those of Example 9, which will not be repeated here.

[0149] Embodiment 15

[0150] The present embodiment provides a high bio-based elastomer tire apex rubber, wherein the formula of the high bio-based elastomer tire apex rubber composition is different from that of Example 9 in that the super vulcanizing agent DES is obtained by co-melting zinc chloride, choline chloride and thiourea in a molar ratio of 1:1:2, and other raw materials and methods are the same as those of Example 9, which will not be repeated here.

[0151] Example 16

[0152] The present embodiment provides a high bio-based elastomer tire apex rubber, wherein the formula of the high bio-based elastomer tire apex rubber composition is different from that of Example 9 in that the super vulcanizing agent DES is obtained by co-melting zinc chloride, choline chloride and thiourea in a molar ratio of 1:1:1, and other raw materials and methods are the same as those of Example 9, which will not be repeated here.

[0153] Comparative Example 3

[0154] This comparative example provides a high bio-based elastomer tire apex rubber, wherein the formula of the high bio-based elastomer tire apex rubber composition is different from that of Example 9 in that an equal amount of natural mineral powder is used to replace the porous three-phase alloy, and other raw materials and methods are the same as those of Example 9, which will not be repeated here.

[0155] Comparative Example 4

[0156] This comparative example provides a high bio-based elastomer tire apex rubber, wherein the formula of the high bio-based elastomer tire apex rubber composition is different from that of Example 9 in that no porous three-phase alloy is added, and other raw materials and methods are the same as those of Example 9, which will not be repeated here.

[0157] Examples 9 to 16 and Comparative Examples 1 to 4 were prepared according to the following preparation method:

[0158] First masterbatch: Start the internal mixer, set the speed to 45-55 rpm, add natural rubber, porous three-phase alloy, rice husk ash white carbon (or carbon black), silane coupling agent, activator, antioxidant and tackifying resin according to the formula, mix for 40 seconds, remove the plug and press the plug to mix for 25 seconds, remove the plug and press the plug to mix until the temperature reaches 147°C for rubber discharge to obtain the first masterbatch.

[0159] Second masterbatch: Start the internal mixer and set the speed to 25-35 rpm. First add the first masterbatch and mix for 40 seconds. Then mix for 25 seconds with the plug raised and the plug pressed. Then mix until the temperature reaches 140℃ and the rubber is discharged to obtain the second masterbatch.

[0160] Apex rubber: Start the internal mixer and set the speed to 25-35 rpm. First add the second masterbatch, insoluble sulfur, accelerator and super vulcanizing agent DES and mix for 40 seconds. Then mix for 25 seconds with the bolt removed and the bolt pressed. Then mix until the temperature reaches 100°C and discharge the glue to obtain a highly bio-based elastomer apex rubber.

[0161] Test Example 2

[0162] During the preparation of apex rubber in Examples 9 to 16 and Comparative Examples 1 to 4, the rubber was tested, including low Mooney value ML, high Mooney value MH, Ts2 time, 10% vulcanization time TC10, 30% vulcanization time TC30, 60% vulcanization time TC60, 90% vulcanization time TC90 and R97 index.

[0163] The test conditions are 151℃*60min.

[0164] The obtained data are shown in Table 4 below.

[0165] Table 4

[0166]

[0167] As can be seen from Table 4, Example 9 and Comparative Example 1 show that the use of super vulcanization aid DES can effectively solve the sulfur rate problem without affecting the MH value. Example 9 and Comparative Example 3 show that the MH value of natural mineral powder is low.

[0168] Test Example 3

[0169] The physical properties and dynamic mechanical properties of the apex rubbers obtained in Examples 9 to 16 and Comparative Examples 1 to 4 were tested.

[0170] Specifically, it includes 300% elongation stress M300, tensile strength TB, elongation at break EB% and tangent value of loss angle tanδ / 60℃ at 60℃.

[0171] 300% elongation stress M300 is carried out in accordance with the provisions of GB / T528-1998; tensile strength TB is carried out in accordance with the provisions of GB / T528-1998; elongation at break EB% is carried out in accordance with the provisions of GB / T528-1998; the tangent value of the loss angle at 60°C, tanδ / 60°C, is carried out under the conditions of frequency 20Hz and strain 10%±2.

[0172] The test data are shown in Table 5 below.

[0173] Table 5

[0174]

[0175] It can be seen from Table 5 that the use of ore powder has low elongation and high heat generation; removing the porous three-phase alloy will reduce the elongation of the rubber.

[0176] Test Example 4

[0177] The thermal conductivity of the apex rubbers obtained in Examples 9 to 16 and Comparative Examples 1 to 4 was tested.

[0178] Specifically, the thermal conductivity λ and the thermal diffusion coefficient α, wherein the thermal conductivity λ is carried out in accordance with the provisions in GB T 11205-2009; the thermal diffusion coefficient α is carried out in accordance with the provisions in GB T 11205-2009.

[0179] The test data are shown in Table 6 below.

[0180] Table 6

[0181]

[0182] It can be seen from Table 6 that the use of porous three-phase alloy can achieve the same thermal conductivity as carbon black, and the use of rice husk ash white carbon black will reduce the thermal conductivity.

[0183] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. Application of a porous three-phase alloy in the preparation of a high bio-based elastomer tire apex rubber composition; The porous three-phase alloy is obtained by high-temperature jetting of carbon black and natural ore powder; The mass content of silicon dioxide in the natural ore powder is 40-60%, and the mass content of aluminum oxide is 30-40%; The natural ore powder has a rich microporous structure and a specific surface area of ​​30-70m 2 / g, pore volume 0.20~0.40cm 3 / g, the number of pores is 100-300 million / g, and the D50 particle size is 0.25-5μm; The mass ratio of carbon black to natural ore powder is 5-9:1-5; The high temperature jet process comprises: The natural ore powder suspension mixed by the jet system is sprayed into the carbon black reaction furnace, and the carbon black reacts with the natural ore powder to form an aluminum-silicon-carbon structure, and then forms an aluminum-silicon-carbon aggregate through aggregation to obtain the porous three-phase alloy; The concentration of the natural ore powder suspension is 15-25wt.%; The injection flow rate of the natural ore powder suspension is 4000-6000 kg / h; The reaction temperature is 1000-1500°C.

2. The use according to claim 1, characterized in that: The grades of the carbon black include at least one of N134, N220, N234, N330, N375 and N550.

3. A high bio-based elastomer tire apex rubber composition, characterized in that: In parts by weight, the composition comprises: 100 parts of natural rubber, 5-20 parts of the porous three-phase alloy according to claim 1 or 2, 20-40 parts of rice husk gray white carbon black, 1-4 parts of silane coupling agent, 3-6 parts of activator, 2-6 parts of antioxidant, 1-3 parts of tackifying resin, 2.5-4.7 parts of insoluble sulfur, 0.8-1.5 parts of accelerator and 0.1-0.5 parts of super vulcanizing aid.

4. The high bio-based elastomer tire apex rubber composition according to claim 3, characterized in that: The super vulcanization aid is a deep eutectic solvent; The super vulcanization aid is prepared from zinc chloride, choline chloride and thiourea in a molar ratio of 1-3:1-3:3-6.

5. The high bio-based elastomer tire apex rubber composition according to claim 3, characterized in that: The specific surface area of ​​the rice husk gray carbon black is 165~240m 2 / g, particle size is 0.8~7.8μm; The brand of the silane coupling agent includes at least one of TESPT, Si75 and Si747; The activator comprises stearic acid and / or zinc oxide; The brand of the antioxidant includes at least one of antioxidant 4020, antioxidant RD and antioxidant 4010NA; The tackifying resin comprises at least one of tert-butylphenol-formaldehyde resin, alkylphenol-formaldehyde resin and petroleum resin; The grades of the petroleum resin include C5 and / or C9; The brands of the accelerator include at least one of accelerator NS, accelerator CZ and accelerator DZ.

6. A high bio-based elastomer tire apex rubber, characterized in that: The apex rubber is obtained by mixing the high bio-based elastomer tire apex rubber composition according to any one of claims 3 to 5.

7. The high bio-based elastomer tire apex rubber according to claim 6, characterized in that: The mixing method comprises the following steps: The first masterbatch is obtained by mixing natural rubber, porous three-phase alloy material, rice husk gray carbon black, silane coupling agent, activator, antioxidant and tackifying resin and performing mixing in one step; Then, the first masterbatch is subjected to two-stage mixing to obtain a second masterbatch; Finally, insoluble sulfur, accelerator and super vulcanizing aid are added into the second masterbatch and mixed and then three-stage kneading is performed to obtain high bio-based elastomer tire apex rubber.

8. The high bio-based elastomer tire apex rubber according to claim 7, characterized in that: The first stage of mixing includes mixing for 30-50 seconds, mixing with the bolt raised and the bolt pressed for 20-30 seconds, and then mixing with the bolt raised and the bolt pressed until the temperature reaches 140-155° C. for debonding; The two-stage mixing includes mixing for 30-50 seconds, mixing with the bolt raised and the bolt pressed for 20-30 seconds, and then mixing with the bolt raised and the bolt pressed until the temperature reaches 135-145° C. for debonding; The three-stage mixing includes mixing for 30-50 seconds, mixing with the plug lifted and the plug pressed for 20-30 seconds, and then mixing with the plug lifted and the plug pressed until the temperature reaches 95-105° C. for debonding.

Citation Information

Patent Citations

  • Improved thermal properties of carbon-aluminum composites

    CN102301039A

  • Improved porous bodies comprised of mullite and methods of forming them

    CN104703944A